Professional Reflexivity in Thai Teachers' Understanding of Asperger's Syndrome - Juthathip Kruanopphakhun; Nadh Ditcharoen (National Research Mordova State University, 2022)
Introduction. The aim of this research is to investigate changes in Thai educators' attitudes towards their understanding of Asperger's Syndrome before and after a teacher-training session. Currently, opportunities for professional training regarding Asperger's Syndrome are very scarce in Thai educational communities. Educators may not be able to provide optimum education and guidance for their students with Asperger's Syndrome. Meanwhile, these students' learning outcomes are significantly affected by their educators lacking knowledge of evidence-based intervention methods. Therefore, based on a needs assessment, a teacher-training session was developed to minimize the gaps in pedagogical knowledge and practice. Materials and Methods. A quasi-experimental, embedded mixed-methods design was used to obtain data. This study employed a one-group, pre-test/post-test design, as there were no control groups involved due to the novel learning subject matter. The limitations of the current study - its structure and participant recruitment - were identified and discussed. An availability sampling method was used for this study, resulting in the recruitment of 12 in-service teachers and 32 pre-service teachers from the northeastern region of Thailand. Questionnaires and interviews were used as measurement tools to comprehensively capture participants' learning experiences. For the statistical analysis, the paired sample t-test (alpha = .05) was used. Meanwhile, for the descriptive analysis, the deductive approach was used. Results. Our results corroborate our sequential hypotheses regarding a teacher-training session and educators' perceived levels of understanding of Asperger's Syndrome. The training session was developed with a hypothesis that teachers needed educational opportunities to acquire proper knowledge of Asperger's Syndrome, so that their students could be fully benefited from the pedagogy. As a result of attending the session, a statistically significant increase in correct response rates was indicated. Indeed, this increase in knowledge fulfilled the second hypothesis that by having proper knowledge of Asperger's Syndrome, teachers' professional reflexivity can be improved. Discussion and Conclusion. The outcomes of this study indicate that a teacher-training session has played a crucial role in cultivating Thai educators' understanding of Asperger's Syndrome. The outcomes present an interesting correlation between teachers' knowledge acquisition and their increased professional and personal reflections. Simultaneously, the findings of this study suggest the potential benefits of improving research methodology, including an employment of randomized control trial, a larger sample size, and diversity within the sample population.